Finsler Transnormal Functions and Singular Foliations of Codimension 1 - Raeisidehkordi, Hengameh (2018)
Transnormal functions are generalization of distance functions and this topic has some applications in Physics and real world problems. In this work, some results are generalized from Riemannian case to the Finsler one. Moreover certain new phenomena that happen only in Finsler spaces are discussed. To have a better understanding, certain examples based on the mentioned results in Randers spaces are provided. Moreover, some applications on propagation of waves of fire and water are introduced